Preliminary study on the parasitic helminth fauna on marine fishes in the coastal waters of Hai Phong province - Ngo, Ha Duy; Ha, Nguyen Van; Tu, Nguyen Dinh; Thanh, Nguyen Vu (Academia Journal of Biology, 2012)
Study on the parasitic worms in marine fishes has not been realized in Vietnam for long time. Only in 60th and 70th decades of the last 20th century, Russian parasitologists such as Parukhin, Oshmarin, Mamaev and Lebedev had investigated the helminth fauna of marine fishes in Gulf of Tonkin describing about 80 helminth species. During the January, February, April, July and October, 2008 the study on helminth and crustacean fauna parasiting on marine fishes has been realized in the coastal waters of Hai Phong province. In total, 44 fish species has studied for present seeking of the parasitic worms and crustaceans. Among all studied 44 fish species, 50.0% were infected by monogeneans; 65.9% were infected by trematodes; 15.9% were infected by cestodes; 56.8% were infected by nematodes; 18.2% were infected by acanthocephalans and only 13.7% were infected by parasitic crustaceans. 70 parasitic worms and crustaceans were recorded, belonging to Monogenea, Acanthocephala, Trematoda, Cestoda, Nematoda, Copepoda, Isopoda. Four parasitic crustacean species were found on 7 different marine fish species for the first time in Vietnam.